Forty years of oil price fluctuations: Why the price of oil may still surprise us - Christiane Baumeister; Lutz Kilian (Goethe University Frankfurt, Center for Financial Studies (CFS), 2015)
It has been forty years since the oil crisis of 1973/74. This crisis has been one of the defining economic events of the 1970s and has shaped how many economists think about oil price shocks. In recent years, a large literature on the economic determinants of oil price fluctuations has emerged. Drawing on this literature, we first provide an overview of the causes of all major oil price fluctuations between 1973 and 2014. We then discuss why oil price fluctuations remain difficult to predict, despite economists' improved understanding of oil markets. Unexpected oil price fluctuations are commonly referred to as oil price shocks. We document that, in practice, consumers, policymakers, financial market participants and economists may have different oil price expectations, and that, what may be surprising to some, need not be equally surprising to others.
urn:nbn:de:hebis:30:3-392941
Keywords: Q43; C53; 330; oil market; oil price shock; heterogeneous price expectations; OPEC; peak oil; unconventional oil